The service quality model of LTE technology downlink - Al-Dulaimi A. M. (ХНУРЭ, 2013)
Presents a mathematical model of resource blocks distribution in LTE technology downlink. Offered model aims at providing guaranteed quality of service wireless users by user stations allocating of required transmission rates. Comparative analysis of obtained solutions by using different objective functions. Using various kinds of objective functions in of fered model is directed to resource blocks allocation of minimum downlink or a minimum data transmission rate of each user station. It was found the greatest savings of time frequency resource allows objective function aimed at minimizing number of used resource blocks. The mod el offered in classes of service CoS corresponds to Class B each providing each user station a guaranteed transmission rate, with access to additional (non-guaranteed) bandwidth. Keywords: LTE; mathematical model, required rate, objective function, resource block.